Information System’s experiences of EGERFOOD project making use of it in the education of the database management - Radványi, Tibor; Kovács, Emőd; Kormos, János (Teaching Mathematics and Computer Science, 2010)
We present in this article the background of a developed food safety tracking system searched and formed in the Regional Knowledge Centre of Eszterházy Károly College, the requirements following from this, and by way of the requirements towards the information system appearing expectations. The development of the consumer centre system is a complex task which provides fast and cost-effective information for consumers, food producers and concerned authorities. It accomplishes severe expectations of the tracking system in connection with data security and encryption beside all this. We demonstrate in this article that forming of database model why we chose the general model. We also demonstrate what kind of SQL server we chose for buffer servers and central data warehouse. We wish to support our choosing with the result of done efficiency examinations. It is important viewpoint what kind of database planning principles we base these examinations on and how we match them to the requirements of the system. As software engineers took part in the development effectively from the first minute of the planning of the system, we can examine with what this project work was able to raise students’ qualification and knowledge in addition to the general curricular substance.